Parallel multigrid method for finite element simulations of complex flow problems on locally refined meshes - Kimmritz, Madlen; Richter, Thomas (Numerical linear algebra with applications, 2011)
We present a parallel multigrid solver on locally refined meshes for solving very complex three-dimensional flow problems. Besides describing the parallel implementation in detail, we prove the smoothing property of the suggested iteration for a simple model problem. For demonstration of the efficiency and feasibility of the solver, we show a chemically reactive flow simulation for a Methane burner using detailed chemical reaction modeling. Further, we give the results of an ocean flow simulation. All described methods are implemented in the finite element toolbox Gascoigne. Copyright © 2010 John Wiley & Sons, Ltd.
Published online 28 August 2010
Gesehen am 04.08.2022